2020
DOI: 10.1002/cncr.32797
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of chemoradiotherapy after surgical resection of glioblastoma: Stratification by validated prognostic classification

Abstract: BACKGROUND:Previous studies examining the time to initiate chemoradiation (CRT) after surgical resection of glioblastoma have been conflicting. To better define the effect that the timing of adjuvant treatment may have on outcomes, the authors examined patients within the National Cancer Database (NCDB) stratified by a validated prognostic classification system. METHODS: Patients with glioblastoma in the NCDB who underwent surgery and CRT from 2004 through 2013 were analyzed. Radiation Therapy Oncology Group r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…First, rather than the percentage of extent of resection, clinicians might need to consider the absolute volume of remaining tumour tissue, including both enhancing and non-enhancing tumour tissue [45][46][47] . Second, early (<3 weeks) as opposed to later (3-5 weeks) initiation of postsurgical radiotherapy does not correlate with improved overall survival (OS) 48 . This finding is unexpected because one might predict that a longer time interval between surgery and start of radiotherapy would favour regrowth of the tumour and thus confer a survival disadvantage 47 .…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, rather than the percentage of extent of resection, clinicians might need to consider the absolute volume of remaining tumour tissue, including both enhancing and non-enhancing tumour tissue [45][46][47] . Second, early (<3 weeks) as opposed to later (3-5 weeks) initiation of postsurgical radiotherapy does not correlate with improved overall survival (OS) 48 . This finding is unexpected because one might predict that a longer time interval between surgery and start of radiotherapy would favour regrowth of the tumour and thus confer a survival disadvantage 47 .…”
Section: Recommendationsmentioning
confidence: 99%
“…The timing, dosing and scheduling of radiotherapy are determined by the disease subtype and prognostic factors, including age, KPS and residual tumour volume. Radiotherapy should start within 3-5 weeks after surgery 48 and is commonly administered at 50-60 Gy in 1.8-2 Gy daily fractions. No evidence suggests additional benefit from high-dose versus low-dose radiation in patients with WHO grade 2 gliomas 52 and, for those with higher WHO grade tumours, no data from randomized studies support the use of doses >60 Gy (ref.…”
Section: Radiotherapymentioning
confidence: 99%
“…The impact of timing of subsequent therapy on OS is still unclear. Nevertheless different studies indicate that a delay of more than 42 days should be avoided [7][8][9][10][11][12]. We observed a signi cantly higher mean time to initiation of subsequent therapy and a corresponding higher rate of delay of more than 42 days for patients with an AE.…”
Section: Discussionmentioning
confidence: 55%
“…However, the association of treatment delay of therapy and OS remains controversial. Although the relevance of the exact timing of subsequent therapy remains uncertain, a systemic review [7] and different studies [8][9][10][11][12][13][14] seem to agree that a moderate delay of subsequent chemoradiotherapy does not have a detrimental effect on OS, but a delay of more than 42 days after surgery might be associated with worse OS.…”
Section: Introductionmentioning
confidence: 99%
“…This is a novel nding that to our knowledge has not been previously identi ed among pediatric HGG, though recent studies in adult glioblastoma using the NCDB found similar results [15]. This study is limited in its retrospective design and the nding could be attributed to selection bias with patients demonstrating more aggressive histologies, more concerning imaging ndings or more aggressive clinical course initiating RT earlier.…”
Section: Discussionmentioning
confidence: 58%